The Role of Pregnancy Nutrition in Maternal and Offspring Health - Maslova, Ekaterina (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In pregnancy, maternal nutrition sustains and nourishes the developing child. Imbalances in either the direction of nutritional excess or deficiency can have adverse consequences for child health. In addition, more research now suggests that good pregnancy nutrition influences child health beyond pregnancy and delivery. This includes modifying the risk of child health outcomes as they enter childhood and adulthood through influences on placental development, hormonal pathways, and organ structure and function. Poor pregnancy nutrition may also compromise maternal health during pregnancy, which may have long-term consequences for women's health. Understanding the biological and social mechanisms operating during pregnancy can help in the design of better clinical and public health interventions. This Special Issue on "The Role of Pregnancy Nutrition in Maternal and Offspring Health" includes etiological and mechanistic studies of pregnancy nutrition with short- and long-term maternal and child health outcomes, including original research, narrative reviews, and systematic reviews and meta-analyses. Together, this body of work provides important insights into the influence of dietary patterns, food groups, and nutrients on pregnancy outcomes, and long-term neurodevelopmental, respiratory, and metabolic health in the children. It also highlights nutritional consequences for specific groups of women, including those with pregnancy complications and eating disorders.